Hubungan Tingkat Pengetahuan, Penurunan Tingkat Stres Menjalani Diet, dan Aktivitas Fisik dengan Kadar Gula Darah Diabetes Melitus di Klinik dr. Moch Budi Setiawan - Oktaviolika, Sinta Sari; Rusnoto; Kartikasari, Fitriana (Universitas Pahlawan Tuanku Tambusai, 2025)
According to estimates, there will be 28.6 million cases of diabetes mellitus (DM), a chronic metabolic disease that is fast increasing, in Indonesia by 2045. Blood sugar levels are influenced by a number of factors, including nutrition, stress, and physical exercise. The association between knowledge levels, stress related to diets, and physical activity and blood sugar management in diabetic patients is the main emphasis of this study. This study examines a number of linked topics, including the connection between blood sugar levels in people with diabetes mellitus and knowledge levels, physical activity, and lowering stress levels associated to diets. This study aims to examine the connection between blood sugar levels and awareness of diabetes mellitus. to ascertain how stress and dieting affect blood sugar levels. To assess the impact of physical activity at Dr. Moch Budi Setiawan's Clinic. Type of Research: Quantitative with a correlational approach. Population: Diabetes mellitus patients at Dr. Moch Budi Setiawan's Clinic. Sample: 44 respondents, selected using convenience sampling techniques. Instruments: Questionnaires for knowledge, stress levels, physical activity, and blood sugar level measurement with glucotest. Analysis of Data Spearman's Rank correlation is used in both univariate and bivariate analysis. Anticipated Findings: This study should show that blood sugar regulation is substantially correlated with increased knowledge, reduced stress, and optimal physical activity.